Analisis pengaruh kualitas website (webqual) 4.0 sikuli.umri.ac.id terhadap kepuasan mahasiswa di univeristas muhammadiyah riau - Fauzan, Fauzan Azim; Binangkit, Intan Diane; Ramadhani, Witri; MZ, Nurse Fatimah (Computer Science and Information Technology, 2023)
This research aims to determine student satisfaction with the SiKuli Muhammasiyah Riau University website, which is e-learning at Muhammadiyah Riau University. The population in this study were all students from the Faculty of Teacher Training and Education and the Management Study Program at Muhammadiyah University of Riau. The research sample consisted of 80 students in each study program who were taken using proportional random sampling. The data collection technique uses a questionnaire. Before the questionnaire is used to collect data, the questionnaire is tested for validity and reliability. Test the validity of the analysis instrument used by factor and item score analysis with a total score. The data analysis technique used is descriptive analysis with percentages. The results of research using the Chi Square and Webqual methods of measurement based on quality function deployment (QFD) are to measure the quality of a website based on research instruments that can be recommended into three variables, namely: usability, information quality, and interaction services. All of them are measurements of consumer or user satisfaction with the quality of the website.